Corrigendum to "The burning heart - The Proterozoic geology and geological evolution of the west Musgrave Region, central Australia" [Gondwana Res., Volume 27, Issue 1, January 2015, Pages 64-94] - Howard, H.; Smithies, R.; Kirkland, Chris; Kelsey, D.; Aitken, A.; Wingate, M.; Quentin de Gromard, R.; Spaggiari, C.; Maier, W. (Elsevier Inc., 2015)
Due to an error during revisions, the following captions for Figs. 5 through to 10 in Howard et al. (2015) are out of order.